2022
DOI: 10.47852/bonviewaia2202303
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Self-Supervised Architecture for Semen Quality Prediction Using Environmental and Lifestyle Factors

Ejay Nsugbe

Abstract: Male fertility has been seen to be declining, prompting for more effective and accessible means of its assessment. AI methods have been effective towards predicting semen quality through a questionnaire-based information source comprising a selection of factors from the medical literature which have been seen to influence semen quality. Prior work has seen the application of supervised learning towards the prediction of semen quality, but since supervised learning hinges on the provision of data class labels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Next, on the ground of the difference size at both ends of the edge, a threshold is artificially set, which is mainly used to distinguish the difference in grayscale values between edges and non edges. When the difference between the two ends of the edge is greater than this threshold, it indicates that the position is an edge pixel and can be extracted [20] ( , ) ( , ) ( , ) In edge detection on the ground of the Canny operator, the first step is to perform Gaussian filtering, which mainly uses normally distributed weights to weight and average the image, to smooth the image, decrease image noise and details. Next, it performs gradient calculation of the image, where the gradient of the image represents the edge intensity and direction at each pixel point in the image.…”
Section: Aedge Detection Of Traffic Markings On the Ground Of Image P...mentioning
confidence: 99%
“…Next, on the ground of the difference size at both ends of the edge, a threshold is artificially set, which is mainly used to distinguish the difference in grayscale values between edges and non edges. When the difference between the two ends of the edge is greater than this threshold, it indicates that the position is an edge pixel and can be extracted [20] ( , ) ( , ) ( , ) In edge detection on the ground of the Canny operator, the first step is to perform Gaussian filtering, which mainly uses normally distributed weights to weight and average the image, to smooth the image, decrease image noise and details. Next, it performs gradient calculation of the image, where the gradient of the image represents the edge intensity and direction at each pixel point in the image.…”
Section: Aedge Detection Of Traffic Markings On the Ground Of Image P...mentioning
confidence: 99%
“…The neural network chosen for the study is the eXtreme gradient boosting (XGBoost) algorithm. XGBoost algorithm is an improved decision tree (DT) algorithm, which can deal with a variety of complex and irregular data [20][21][22]. The surrounding rock type (SRT) prediction model constructed by the study is shown in Figure 1.…”
Section: A Xgboost-based Ggpm Model For Underground Coal Minesmentioning
confidence: 99%
“…The application fields of FR models are very extensive, which can be applied in security fields such as access control systems, identity verification, and crime investigation. In addition, FR can also be applied to human-computer interaction and has a wide range of applications [20]. The traditional FR model is shown in Fig.…”
Section: B Fr Model Onmentioning
confidence: 99%